Sistem Informasi Geografis Pencarian Lokasi Service AC Di Kota Medan - Khairuni Syabbrina; Edy Rahman Syahputra; Yulia Agustina Dalimunthe (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
This study aims to build a geographic information system for finding ac service locationsin the city of Medan. The information system is later expected to be able to help provide information in the form of ac service locations in the city of Medan to the public using the website platform. The system development method used in this research is the waterfall. The application is made using the PHP programming language and the database used is MySQL. This study also uses Google Map as a marker of the location of the ac service location search and the direction of the intended ac service location. The results show that the application or system that is built can display the location of the ac service location search and the direction to the location of the ac service that is intended by the user which can help the user (people find the location of the intended ac service). The system can also display information on the ac service store, making it easier for the user (community) to find out the information on the ac service to be addressed